Principles of Ultrasonic Agglomeration and Its Effect on Physicochemical and Macro- and Microstructural Properties of Foods - Rivera-Tobar, D (Elsevier Ltd, 2025)
Ultrasonic compaction, also known as ultrasonic agglomeration, is an emerging technology that represents a novel alternative for food agglomeration; it is of great interest to the food industry. This review aims to gather information on the physicochemical, organoleptic, microbiological, and structural changes generated by ultrasound and study the fundamentals of agglomeration and ultrasound in different food matrices. In addition, chemical changes are reported in some nutrients related to conformational changes, such as the disintegration of diacylglycerides into monoacylglycerols, disordering of the crystalline region of starch granules to the amorphous phase, disruption of the membrane in plant cells, and transient or permanent modification of the protein structure (3D folding). The increasing development of patents can provide an insight into the potential of ultrasonic agglomeration applications in the food industry. © 2024